Media-education: Historical Aspect of Development - Мороз, Ольга Олександрівна (Educological discourse, 2014)
In the article the historical aspect of media-education development is examined. The author emphasizes on the scientific views in relation to determination and essence of media-education, analysis of basic theories and conceptions of its realization.